Tackling smoking among out of school youth in South Africa: An analysis of friendship ties. (December 2019) - Desai, R.; Ruiter, R.A.C.; Schepers, J.; Reddy, S.P.; Mercken, L.A.G.
Abstract: Background: Friendships during adolescence play a significant role in the initiation and maintenance of tobacco use. Smoking behaviour among adolescent friends has not been explored among out of school youth (OSY) in South Africa. Out of school youth (OSY), described as those between 13 and 20 years old, have not completed their schooling and are not currently enrolled in school, are at greater risk for tobacco use. Aim: The main aim of this study is to examine whether the smoking behaviour of OSY is associated with that of their OSY friends. Methods: Respondent driven sampling was used to recruit OSY and their OSY friends. A mixed effects logistic regression with a random intercept across school-province combinations was used to analyse survey data. Race and gender were also incorporated into the analyses as effect moderators ( n  = 391). Results: Results of this study confirm that cigarette smoking was common among OSY and their OSY friends, with 53.5% of the respondents smoking in the past month (SD = 0.44). When OSY friends were either all non-smokers or half their friends were non-smokers, Coloured (mixed race) OSY were less likely to smoke compared to Black African and Other (mostly Asian descent) OSY. Conclusion: Cultural norms and values associated with the different race groups may play a role in the smoking behaviour of out of school youth friends. Understanding this relationship is useful for identifying those OSY that are vulnerable to the behaviours that place them at risk of tobacco related morbidity and mortality. Highlights: Smoking was common among out of school youth and their out of school youth friends. Racial differences were found in out of school youth smoking and their friends. Cultural norms and values influence smoking behaviour of out of school youth friends.